Series resistance effect on the output parameters of buried emitter silicon solar cells - Gamal M. Eldallal; Mohamed Y. Feteha; Mostafa E. Mousaa (International Journal of Photoenergy)
A realistic distributed equivalent circuit for the buried emitter silicon solar cell is presented taking into consideration the carriers paths through the planar and vertical junctions. In addition, a new theoretical model for the cell characteristics including the cell's mismatching, series resistance, different junctions (planar and vertical) and junctions geometry is considered in this work. The results are compared with the published data.